Pipe sizing for district cooling distribution network - Augusto, Gerardo L. (Animo Repository, 2013)
An implicit solution of Colebrook-White equation was developed in calculating the friction factor for commercial steel pipes using iterative approach such as Newton-Raphson method with Reynolds number ranging from 4.0×103 to 5.9×106. The initial value for iterative friction factor estimation was based on expanded form of Colebrook-White equation for larger values of Reynolds number. Numerical results were compared with known explicit solutions and iterative procedure proposed by Lester by evaluating their mean difference, root-mean square deviation, mean relative error and correlation coefficient. Correlation coefficients equal to unity with overall mean relative error of 2.6135x10-8 were achieved for all cases when compared with iterative solution suggested by Lester. It was also found that the use of Hazen-Williams equation for friction factor estimation as an alternative to Colebrook-White equation was strongly discouraged.Combining the subroutine of friction factor identification with the main program that determines the pipe size of distribution network defines the boundaries of chilled-water velocities at different pressure drop limits as a function of commercial steel pipe diameter.